Multi-center outcome analysis of 16 face transplantations - a retrospective OPTN study - Knoedler, Leonard; Schaschinger, Thomas; Niederegger, Tobias; Hundeshagen, Gabriel; Panayi, Adriana C.; Cetrulo, Curtis L.; Jeljeli, Maxime; Hofmann, Elena; Heiland, Max; Koerdt, Steffen; Lellouch, Alexandre G. (Transplant international, 2025)
Facial Vascularized Composite Allotransplantation (fVCA) restores form and function for patients with severe facial disfigurements, yet multi-center outcome data remain scarce. We accessed the Organ Procurement and Transplantation Network (OPTN) database from 2008-2024 to identify all full- or partial-face fVCA recipients, excluding patients under 18 years and those with physiologically impossible BMIs. Of 25 identified patients, 16 (64%) met inclusion criteria (69% male; mean age 43 ± 14 years). Recipients experienced a median of 5 [IQR 0.0-10] acute rejection episodes, which correlated with inotrope use during donor procurement (p=0.033). On average, patients were hospitalized 2.4 ± 1.8 times, with arginine vasopressin (AVP) administration linked to fewer hospitalizations (p=0.035). Seven recipients (44%) experienced complications, and extended-criteria donor (ECD) status was associated with higher complication rates (p=0.049). These findings underscore the promise of fVCA to address complex facial defects while identifying key risk factors—particularly inotrope use and ECD status, while AVP administration may mitigate hospital stays. Further studies with larger cohorts are warranted to refine perioperative strategies, improve outcomes, and expand the clinical utility of fVCA.
Veröffentlicht: 29. Januar 2025
Gesehen am 01.08.2025